Skrining Kesehatan Kulit Remaja Berbasis Sekolah: Analisis Kadar Minyak, Air, dan Hidrasi Kulit di SMA Tarakanita Citra Raya - Moniaga, Catharina Sagita; Santoso, Alexander Halim; Gunaidi, Farell Christian; Abizar Rafi, Muhammad Adam; Dava Pratama, Muhammad Kevin (Westscience Press, 2025)
Adolescence is a transitional period that is highly susceptible to various skin problems due to hormonal changes, environmental exposure, and suboptimal skincare habits. This community service activity aimed to assess the skin health status of adolescents through screening of skin oil, water, and hydration levels using a digital skin analyzer. The activity was conducted at SMA Tarakanita Citra Raya, involving 144 students as respondents. Skin assessments were performed on the forearm using a standardized tool, with results categorized into clinical classifications: dry, neutral, and oily for oil level; dry, neutral, and excessive for water level; and five hydration categories ranging from dry to moist. The findings indicated that the majority of respondents were 16 years old (55.6%), with females comprising a slightly higher proportion (54.2%). A total of 45.8% were classified as having dry skin based on oil levels, and 49.3% had low water content in their skin. However, hydration status was found to be optimal in 95.8% of the participants. These results suggest a physiological imbalance between sebum levels and skin moisture, underlining the need for continuous education on appropriate skincare practices. This screening activity demonstrates significant potential as a promotive and preventive intervention to support adolescent skin health within the school setting.